СПОРТ ФАОЛИЯТИ ЖАРАЁНИДА КУРАШЧИЛАРНИНГ МАШҒУЛОТ ВА МУСОБАҚА ЮКЛАМАЛАРИГА МОСЛАШИШИ МУАММОЛАРИ - Еримбетов, Б.Қ. (SCIENCE and SOCIETY, 2020)
This article presents the results of the study of the problems of adaptation of training and competitive loads in the process of sports activity of kurashists.
Keywords: kurash; training of kurashists; sports events; competitive loads; training management; adaptation